Programação da produção em ambientes de manufatura aditiva: análise do estado-da-arte e proposta de método de resolução - Dall'Agnol, Gabriela (Universidade Federal de São Carlos, 2023)
With the advancement of production technologies and materials, it is currently possible to use Additive Manufacturing (AM), also known as 3D printing, for the large-scale production of finished products, with numerous advantages, such as a high level of customization, simplification of factory floor and fast delivery. Production sequencing, known as Scheduling, is a well-established topic in his research area, but its application within an AM environment faces specific issues that have yet to be explored by researchers. The present study carries out a Systematic Literature Review (SLR) on the subject, in order to identify the main mathematical models, algorithms adopted for their solution and the main characteristics of the computational experiments carried out. The considered environment was mathematically modeled and, subsequently, a constructive heuristic solution multi-start based on the GRASP algorithm (Greedy Randomized Adaptive Search Procedure) was implemented in order to solve this problem. From generated instances, its performance was evaluated through computational experiments. The results showed that the proposed heuristic managed to obtain good results in very little computational time, in addition to achieving a low gap dispersion, indicating a high repeatability of the implemented heuristic.
Scheduling in additive manufacturing environments: state-of-the-art analysis and proposed resolution method
Keywords: Manufatura aditiva; Heurísticas; Meta-heurísticas; Modelagem matemática; Scheduling; Additive manufacturing; Heuristics; Meta-heuristics; Mathematical modeling; ENGENHARIAS::ENGENHARIA DE PRODUCAO::PESQUISA OPERACIONAL